Twin deficits in Cambodia: Are there Reasons for Concern? An Empirical Study - Evan, Lau; Tuck Cheong, Tang (Monash University, 2009)
This study examines the inter-linkages between Government budget balance, and external balance for a transition economy in South East Asia – Cambodia. The empirical results of the quarterly data between 1996 and 2006, support twin deficits hypothesis that is the budget deficits do cause external deficits, in the short run. These two macroeconomics variables are moving together in the long run. For implication, these findings provide an insight for the Cambodia’s policy design and formulation.